Fluid Balance, Hydration, and Athletic Performance - Meyer, Flavia; Szygula, Zbigniew; Wilk, Boguslaw (Taylor & Francis, 2016)
Athletes and nonathletes frequently consume too little water or fluids, affecting exercise performance as well as overall health. This book comprehensively reviews the aspects relating to body fluid balance, rehydration, and physical exercise. It provides background on body water balance and turnover, topics related to electrolyte balance, and sweating as the basis for thermoregulatory and fluid homeostasis during exercise. In addition, chapters cover body water balance evaluation and regulation; cardiovascular and metabolic responses to fluid imbalance; effects of dehydration on aerobic power, muscle strength, and cognitive function; fluid intake timing; and optimal beverage selection.